Conflict Resolution for Mesozoic Mammals: Reconciling Phylogenetic Incongruence Among Anatomical Regions - Celik, Mélina A.; Phillips, Matthew J. (Frontiers in Genetics, 2020)
The evolutionary history of Mesozoic mammaliaformes is well-studied. Although the backbone of their phylogeny is well resolved, the placement of ecologically specialized groups has remained uncertain. Functional and developmental covariation has long been identified as an important source of phylogenetic error, yet combining incongruent morphological characters all together is currently a common practice when reconstructing phylogenetic relationships. Ignoring incongruence may inflate confidence in reconstructing relationships, particularly for the placement of highly derived and ecologically specialized taxa, such as among australosphenidans (particularly crown monotremes), haramiyidans and multituberculates. The alternative placement of these highly derived clades can alter the taxonomic constituency and temporal origin of the mammalian crown group. Based on prior hypotheses and correlated homoplasy analyses, we identified cheek teeth and shoulder girdle character complexes as having high potential to introduce phylogenetic error. We showed that incongruence among mandibulodental, cranial and postcranial anatomical partitions for the placement of the australosphenidans, haramiyids and multituberculates could largely be explained by apparently non-phylogenetic covariance from cheek teeth and shoulder girdle characters. Excluding these character complexes brought agreement between anatomical regions and improved confidence in tree topology. These results emphasize the importance of considering and ameliorating major sources of bias in morphological data, and we anticipate will be valuable for confidently integrating morphological and molecular data in phylogenetic and dating analyses.